Ulva Compressa from Copper-Polluted Sites Exhibits Intracellular Copper Accumulation, Increased Expression of Metallothioneins and Copper-Containing Nanoparticles in Chloroplasts - Moenne-Munoz, A; Segura-Segura, R; Segura-Segura, R; Gonzalez-Bustamante, B; Pizarro-Reyes, J; Pizarro-Reyes, J; Espinoza-Majmud, D (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
In order to analyze the mechanisms involved in copper accumulation in Ulva compressa, algae were collected at control sites of central and northern Chile, and at two copper-polluted sites of northern Chile. The level of intracellular copper, reduced glutathione (GSH), phytochelatins (PCs), PC2 and PC4, and transcripts encoding metallothioneins (MTs) of U. compressa, UcMT1, UcMT2 and UcMT3, were determined. Algae of control sites contained around 20 μg of copper g−1 of dry tissue (DT) whereas algae of copper-polluted sites contained 260 and 272 μg of copper g−1 of DT. Algae of control sites and copper-polluted sites did not show detectable amounts of GSH, the level of PC2 did not change among sites whereas PC4 was increased in one of the copper-polluted sites. The level of transcripts of UcMT1 and UcMT2 were increased in algae of copper-polluted sites, but the level of UcMT3 did not change. Algae of a control site and a copper-polluted site were vis-ualized by transmission electron microscopy (TEM) and the existence of copper in electrodense particles was analyzed using energy dispersive x-ray spectroscopy (EDXS). Algae of copper-polluted sites showed electrodense nanoparticles containing copper in the chloroplasts, whereas algae of control sites did not. Algae of a control site, Cachagua, were cultivated without copper (control) and with 10 μM copper for 5 days and they were analyzed by TEM-EDXS. Algae cultivated with copper showed copper-containing nanoparticles in the chloroplast whereas control algae did not. Thus, U. compressa from copper-polluted sites exhibits intracellular copper accumulation, an increase in the level of PC4 and expression of UcMTs, and the accumulation of copper-containing particles in chlo-roplasts. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.